Development of biology learning media based on video blogs (vlog) on environmental change topic - Nudiya Varisa; Achmad Ali Fikri (Universitas Muhammadiyah Malang, 2022)
Until now, the use of technology-based media is still not optimally used to overcome problems in the biology learning process. The purpose of this study was to develop a vlog-based Biology learning media on environmental change topic and to test the validity and practicality of the media. This Research and Development (R&D) used the ADDIE development model. The learning media developed contains materials, videos, pictures and evaluations that allow students to learn independently. vlog-based Biology learning media developed and created using the Capcut application, then uploaded to the YouTube. The score from the results of the media expert's validation reached 72.9% in the valid category, while the material expert reached 86.8% with the very valid category. The vlog media was declared practical based on the assessment of teachers and students because it reached 77.65%. The vlog-based media that has been developed in this study is expected to be used as a learning media for teachers when teaching environmental change topic.